Sistem Pendukung Keputusan Penyeleksian Mekanik Menjadi Seorang SA (Service Advisor) Menggunakan Metode Moosra - Ahmad Safitra; Pristiwanto Pristiwanto; Rian Syahputra (Journal of Informatics, Electrical and Electronics Engineering, 2021)
-Mechanical selection is the process of selecting the best mechanic according to certain criteria. This process is carried out to raise the level or level of a mechanic to become a service advisor. As is well known, it is not easy to choose the right person to be promoted to a certain position, especially for this, it is necessary to record an analysis of information from the data held by that person since entering the company, to planning education and what opportunities/challenges are needed. given to the mechanic if he wants to be projected on a certain position. SA (Service Advisor) is a person who carries out a consulting function for consumers who come to the workshop to perform services and has a responsibility to achieve unit entry targets every month. His job is to explain to the customer what actions will be taken in connection with the condition of the car that will enter the workshop. Therefore, to determine a Service Advisor, a decision support system with the MOSOORA method is needed, which is expected to assist in the selection. Multi-objective Optimization Method On the basis of simple ration analysis is one of the multi-objective optimization methods